The meaning of 1 John 3:9 with reference to 1 John 1:8 and 10 - Kotze, P.P.A. (Neotestamentica, 1979)
1 John 3:9 with reference to 1 John 1:8 and 10 in Greek.
free
Keywords: 1 John 1:8 and 10; 1 John 3:9; Greek